Happiness in action: the impact of positive affect on the time of the conscious intention to act - Rigoni, Davide; Demanet, Jelle; Sartori, Giuseppe (Frontiers in Psychology, 2015)
The temporal relationship between our conscious intentions to act and the action itself has been widely investigated. Previous research consistently shows that the motor intention enters awareness a few hundred milliseconds before movement onset. As research in other domains has shown that most behavior is affected by the emotional state people are in, it is remarkable that the role of emotional states on intention awareness has never been investigated. Here we tested the hypothesis that positive and negative affects have opposite effects on the temporal relationship between the conscious intention to act and the action itself. A mood induction procedure that combined guided imagery and music listening was employed to induce positive, negative, or neutral affective states. After each mood induction session, participants were asked to execute voluntary self-paced movements and to report when they formed the intention to act. Exposure to pleasant material, as compared to exposure to unpleasant material, enhanced positive affect and dampened negative affect. Importantly, in the positive affect condition participants reported their intention to act earlier in time with respect to action onset, as compared to when they were in the negative or in the neutral affect conditions. Conversely the reported time of the intention to act when participants experienced negative affect did not differ significantly from the neutral condition. These findings suggest that the temporal relationship between the conscious intention to act and the action itself is malleable to changes in affective states and may indicate that positive affect enhances intentional awareness.